2015
DOI: 10.5812/traumamon.13530
|View full text |Cite
|
Sign up to set email alerts
|

Propofol versus Midazolam for Procedural Sedation of Anterior Shoulder Dislocation in Emergency Department

Abstract: Background:Anterior shoulder dislocation (ASD) is one of the most common reasons for referrals to emergency departments (ED). Usually, a combination of an intravenous narcotic and a benzodiazepine is used for procedural sedation and analgesia (PSA) in such cases.Objectives:This study compares the efficacy of two combinations to reduce ASD.Patients and Methods:The subjects in this clinical trial consisted of 48 patients with ASD who were randomly assigned to midazolam/fentanyl and propofol/fentanyl groups for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…The finding could be explained by deeper levels of sedation for propofol and more prolonged sedation for midazolam. The current study findings were similar to previous reports in this field (21-23).…”
Section: Discussionsupporting
confidence: 93%
“…The finding could be explained by deeper levels of sedation for propofol and more prolonged sedation for midazolam. The current study findings were similar to previous reports in this field (21-23).…”
Section: Discussionsupporting
confidence: 93%
“…Ultimately, we observed that administration of propofol or midazolam did not change the incidence rates of nausea and vomiting. This finding is consistent with those of other studies ( 31 ).…”
Section: Discussionsupporting
confidence: 94%
“…Even though the patients' prolonged stays at the crowded emergency departments are not preferred, providing patient comfort and the sufficient muscle relaxation might decrease the possible complications. In the literature, proper monitorization and airway management together with the application of intravenous analgesia and a sedative agent were recommended as a proper method for sufficient sedation in shoulder dislocations (14,15).…”
Section: Discussionmentioning
confidence: 99%